The roots of female emancipation: From perennial cool water via pre-industrial late marriages to postindustrial gender equality - Manuel Santos Silva; Amy C. Alexander; Stephan Klasen; Christian Welzel (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Reviewing the burgeoning literature on the deep historic roots of gender inequality, we theorize and provide evidence for an overlooked trajectory that (1) originates in a climatic configuration called the "Cool Water" (CW-) condition, from where the trajectory leads to (2) late female marriages in pre-industrial times, which eventually pave the way towards (3) various gender-egalitarian outcomes today. The CW-condition is a specific climatic configuration that combines periodically frosty winters with mildly warm summers under the ubiquitous accessibility of fresh water. The CW-condition is most prevalent in Northwestern Europe and its former colonial offshoots and embodies opportunity endowments that significantly reduce fertility pressures on women, which favored late female marriages already in the pre-industrial era. The resulting family and household patterns placed women into a better position to struggle for more gender equality during the subsequent transitions toward the industrial and post-industrial stages of development. Hence, enduring territorial differences in the CW-condition predict differences in pre-industrial female marriage ages, which in turn explain differences in gender equality today. The role of CW retains significance along this causal chain after controlling for other 'deep drivers' of gender inequality that have been discussed in the literature. We summarize these findings in a "seed theory of female emancipation" and conclude with a discussion of its broader implications.
Keywords: J12; J16; N30; O15; 330; Cool water; Economic development; Gender equality; Historic drivers; Seed theory